Device-Measured Physical Activity, Sedentary Behaviors, Built Environment, and Adiposity Gain in Older Women: A Seven-Year Prospective Study - Molina-Garcia, Pablo; Medrano, María; Pelclová, Jana; Zając-Gawlak, Izabela; Tlučáková, Lenka; Přidalová, Miroslava (International journal of environmental research and public health, 2021)
The search for determinants of adiposity gain in older women has become vitally important. This study aimed to (1) analyze the adiposity gain based on the participants' age and (2) determine the prospective associations of baseline intrapersonal, built environment, physical activity, and sedentary behavior variables with the adiposity gain in older women. This was a seven-year prospective study (baseline: 2009 to 2012; follow-up: 2016 to 2019) in older women (n = 178, baseline age = 62.8 ± 4.1 years). Baseline and follow-up adiposity (bioelectrical impedance) and baseline physical activity, sedentary behavior (accelerometers), and intrapersonal and built environment (Neighborhood Environment Walkability Scale questionnaire) variables were included. The body mass index (BMI) increment tended to be inversely associated with the women's age (p = 0.062). At follow-up, 48, 57, and 54% of the women had a relevant increase (d-Cohen > 0.2) in their BMI, percentage of body fat, and fat mass index, respectively. The women that spent ≥8 h/day being sedentary were 2.2 times (1.159 to 4.327 CI95%, p < 0.02) more likely to increase BMI (0.82 to 0.85 kg/m2) than non-sedentary women. No built environment variables were associated with seven-year adiposity gain (all ps > 0.05). A reduction in sedentary time should be promoted for adiposity gain prevention and health preservation in older women.
Keywords: Sedentary Behavior; Female; ženské pohlaví; sedavý životní styl; průřezové studie; neighborhood environment walkability scale; lidé; cvičení; Adiposity; Built Environment; adipozita; accelerometer; prospektivní studie; Cross-Sectional Studies; Aged; Prospective Studies; body mass index; index tělesné hmotnosti; fat mass; lidé středního věku; senioři; vytvořené prostředí; Body Mass Index; Exercise; Middle Aged; Humans